Features of local self-government in the Steppe general government - I. A. Konovalov (Правоприменение)
The subject. Many shortcomings in the current state of local government and self-government systems are that in the process of forming institutions of public power, there were not evolutionary qualitative changes, but, on the contrary, there were processes of quantitative complication of mechanisms and institutions for the exercise of public power, making the role of the people in administrative processes impossible or insignificant.The theoretical and methodological basis of the research are the categories and principles of materialistic dialectics, systematic, formal-logical, formal-legal and comparative-legal methods.The main results. The article discusses 4 types of self-government that existed in the Steppe General Government in the prerevolutionary period. Special attention is paid to organizational and legal issues, the structure and forms of activity of urban, peasant, Cossack and Kyrgyz (Kazakh) self-government, their interaction with local administrative and police bodies represented by the Governor-General, regional governors and county chiefs. Conclusions. The activity of local self-government bodies in the Steppe Region was based on the concept of self-government, which was based on the fact that local self-government had to act in the interests of state power. It carried out its activities on the basis of laws, the subjects of its jurisdiction and competence were also determined by the state. The activities and powers of the local state administration and local self-government were considered homogeneous and constituted a single power vertical.